2015
DOI: 10.1103/physreve.91.023106
|View full text |Cite
|
Sign up to set email alerts
|

Equations of state, transport properties, and compositions of argon plasma: Combination of self-consistent fluid variation theory and linear response theory

Abstract: A consistent theoretical model that can be applied in a wide range of densities and temperatures is necessary for understanding the variation of a material's properties during compression and heating. Taking argon as an example, we show that the combination of self-consistent fluid variational theory and linear response theory is a promising route for studying warm dense matter. Following this route, the compositions, equations of state, and transport properties of argon plasma are calculated in a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…To further exclude this possibility, a series of FTDFT+MD calculations are carried out surrounding the experimental density and temperature. Based on previous theoretical estimations 4 11 22 , which predicted that Mott effect took place at a length scale comparable to the diameter of the outer-most electronic orbitals, we consider the density between 1 g/cm 3 and 8.34 g/cm 3 . The upper limit of 8.34 g/cm 3 corresponds to an average atomic distance ~2 Å, slightly larger than the diameter d = 1.94 Å of the 3 p orbital for an isolated Ar atom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further exclude this possibility, a series of FTDFT+MD calculations are carried out surrounding the experimental density and temperature. Based on previous theoretical estimations 4 11 22 , which predicted that Mott effect took place at a length scale comparable to the diameter of the outer-most electronic orbitals, we consider the density between 1 g/cm 3 and 8.34 g/cm 3 . The upper limit of 8.34 g/cm 3 corresponds to an average atomic distance ~2 Å, slightly larger than the diameter d = 1.94 Å of the 3 p orbital for an isolated Ar atom.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature concerned is between 10 3 K and 2 × 10 4 K. Higher temperature is not considered because both theories and experiments showed that Mott effect prefers lower temperature. It can only take place below some critical temperature 4 11 12 13 21 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, X-ray lasers can be used to probe the ion structure, electronic charge states, thermodynamic, and optical properties of dense plasmas [6]. Equations of state, compositions, transport and optical properties of dense plasmas [7,8] are also needed for radiation hydrodynamic simulations as well as for interpretation of plasma emission spectra.…”
Section: Introductionmentioning
confidence: 99%